Working safely on de-energized equipment - Knowlton, Robert A. (Texas : Gulf Publishing Company, 1993)
This program highlight on special problem of working with de-energized works and how to handle it.
Narrator: Robert A. Knowlton
Keywords: Energy industries; Industries -- Power supply; Industrial equipment industry; Energy conservation equipment industry